SISTEM PENDETEKSI KAPASITAS TEMPAT SAMPAH SECARA OTOMATIS PADA KOMPLEKS PERUMAHAN - Surjati, Indra; Wijono, F.X. Sigit; Suherman, Suherman (TESLA Jurnal Teknik Elektro UNTAR, 2008)
Automatic Trash Capacity Detection System for Real Estate, there are two parts including: transmitter unit part and receiver unit part by alternating communication. The both of parts working by wireless using Radio Frequency wave. The transmitter unit part there are Infrared Sensors module, Microcontroller module, Modulator of Frequency Shift Keying module, and Transmitter of Frequency Modulation module. While on receiver unit there are Receiver of Frequency Modulation module, Demodulator of Frequency Shift Keying Module, Microcontroller module, Interfacing module, and Personal Computer for monitoring and database view.